Influence of cement particle size, ultra-fine fly ash, and ultra-fine silica fume on the physical and microscopic properties of slurry - Kai Wang; Siyang Guo; Hua Yuan; Jiahui Ren; Pengyu Chen; Qihao Zhang (Case Studies in Construction Materials)
Considering the rapid development of the engineering industry, cement grouting materials are critical in many projects. However, cement production is energy-intensive and relies on non-renewable raw materials. To achieve sustainable development and low-carbon living, the development of an environmentally friendly and high-performance cement grouting material is essential. Fly ash and silica fume have been considered additives to cement to make it more environmentally friendly, but an optimal ratio of these additives has not been found. In this study, the effects of ultrafine cement (UC), ultra-fine fly ash (UFA), and ultra-fine silica fume (USF) on the flowability, stability, and compressive strength of composite cement slurries were investigated. Tests were conducted to determine the shear force, apparent viscosity, water evolution rate, and compressive strength. Microscopic analyses of the cement containing UFA and USF were performed using X-ray diffraction and scanning electron microscopy. The experimental results demonstrate that UFA improves the fluidity and stability of the slurry but reduces its strength; the optimal dosage is 10 %–30 %. USF reduces the fluidity of the slurry but improves its stability and compressive strength; the optimal dosage is 3 %–10 %. UFA and USF improve the microstructure of the cement surface. After adding UFA, cement hydration accelerates, and more calcium silicate hydrate (C-S-H) is generated in the later stage. Therefore, replacing cement with UFA and USF can reduce cement consumption and improve performance. Finally, using orthogonal experiments, the optimal slurry ratio with comprehensive performance was selected as follows: UC of K1340, 0.7 W/C, 30 % UFA, 10 % USF, and 1 % water reducer. This study provides valuable insights and practical guidelines that can enhance the performance, sustainability, and cost-effectiveness of cement grouting materials used in various engineering applications.